Fragments of viral surface proteins modulate innate immune responses via formyl peptide receptors - Heiko Heilmann; Lukas Busch; Celine Buchmann; Islam Mohamed; Adrian Theiß; Sabryna Junker; Stefan Lohse; Bernd Bufe (iScience, 2025)
Summary: Formyl peptide receptors (FPRs) are pattern recognition receptors well-known for bacterial pathogen sensing. We here identified activator and inhibitor motifs for FPRs that are present on surface proteins of various viral pathogens. Peptides containing these motifs interact with all FPR family members and modulate various important immune functions in innate immune cells. Viral breakdown products comprising these motifs were found in patients with COVID-19. In the spike protein, many activators are found in highly mutagenic regions, whereas the inhibitor motif is located in a conserved domain that also exists in further unrelated viruses. The physiochemical properties of FPR1 activators correlate with the occurrence of protein aggregation hotspots. Such hotspots are present on various surface proteins of unrelated viruses that can also activate FPRs. This points toward a general contribution of FPRs in modulating antiviral immune responses during many distinct viral infections.